AN ANALYSIS OF POLICY COMPATIBILITY BETWEEN CONVENTIONAL INSURANCE AND ISLAMIC INSURANCE POLICIES: A STUDY OF CONCEPTUAL AND OPERATIONAL DIFFERENCES - Mohamed Mazahir, Seyed Mohamed; Ab Rahman, Asmak; Ramzy, Mohammad Ismath (Jurnal Syariah, 2017)
The aim of this study is to compare and contrast conventional insurance policies from Islamic insurance policies (takÄful) using a qualitative method consisting of a descriptive and narrative analysis. This study makes a case for takÄful as complimentary to conventional insurance. However, the differences between Islamic and conventional insurance are found mainly in their conceptual framework, how governments regulate them, corporate ownership and financing, management, accounting systems, and how premiums are invested. Both conventional and Islamic insurance are similar in this regard and are both utilized as safety nets in the event of unforeseen incidents. However, to maintain the integrity of Islamic law and Muslim society, insurance practices must be tailored to further comply with the Shariah principles.